Stress, its determinants and its association with academic performance among the students of a medical college in Kerala - M Madhusudan; Sudarshan B Puttaswamy; K M Anjali Krishna; P K Farsana; A S Angela; I Muneer; Tessy Thomas (Wolters Kluwer Medknow Publications, 2020)
Introduction: Medical education is one of the most stressful academic curricula worldwide, negatively affecting the health of medical students. Stress in medical students if not tackled in time, can have professional ramifications, as well as personal consequences. Hence, in this background, this study was undertaken to find out the prevalence of stress among medical students, its determinants and its association with academic performance. Material and Methods: This was a cross-sectional study done at a medical college, Wayanad district, between January and June 2019. All the undergraduate medical students of the college were the study subjects. Data were collected using a predesigned and pretested self-administered questionnaire, the first part of which had questions pertaining to basic sociodemographic details, factors affecting stress, and their academic performance, and the second part was the Medical Student Stress Questionnaire. Completed responses were obtained from a total of 605 students. Results: About 29.8%, 53.6%, 16.7% and 0% were found to have no/mild stress, moderate stress, high stress and severe stress respectively. The prevalence of moderate/high stress was more among 25-26 years, males, married, Phase I MBBS, government quota, Muslim, urban origin, and day scholar students. However, only religion and place of origin were found to have a significant association (P = <0.01 and 0.048 respectively). The median stress score was highest for the academic domain 1.5 and least for drive and desire related and group activities related domain (1 for both). There was a very weak positive correlation (r = 0.007) between the percentage of marks obtained and total stress scores, and the correlation was found to be statistically insignificant (P = 0.868). Conclusion: The prevalence of stress among the participants was low. Muslim religion and urban origin were found to have a significant association with the prevalence of moderate/high stress. There was a very weak positive correlation between the percentage of marks obtained and total stress scores.